2007
DOI: 10.1063/1.2742324
|View full text |Cite
|
Sign up to set email alerts
|

Selective toxicity of zinc oxide nanoparticles to prokaryotic and eukaryotic systems

Abstract: We report on the toxicity of ZnO nanoparticles (NPs) to gram-negative and gram-positive bacterial systems, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), and primary human immune cells. ZnO NP (~13 nm) showed complete inhibition of E. coli growth at concentrations 3.4 mM, whereas growth of S. aureus was completely inhibited for 1 mM. Parallel experiments using flow cytometry based assays clearly demonstrated that growth inhibitory properties of ZnO NP were accompanied by a corresponding loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
468
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(531 citation statements)
references
References 13 publications
27
468
1
6
Order By: Relevance
“…5. However, in comparison to various reports on nanostructures of Ag, Pd, Fe-Pt, TiO 2 , ZnO, MgO, CuO, etc., the MIC and MIB values in present study are low (Peng et al 2002;Xie et al 2011;Stoimenov et al 2002;Morones et al 2005;Ruparelia et al 2007;Maenosono et al 2007;Tsuang et al 2008;Reddy et al 2007;Heinlaan et al 2008;De Windt et al 2006;Lyon et al 2005). Besides, they exhibit biofilm inhibition.…”
Section: Msns Synthesis and Physico-chemical Characterizationmentioning
confidence: 44%
“…5. However, in comparison to various reports on nanostructures of Ag, Pd, Fe-Pt, TiO 2 , ZnO, MgO, CuO, etc., the MIC and MIB values in present study are low (Peng et al 2002;Xie et al 2011;Stoimenov et al 2002;Morones et al 2005;Ruparelia et al 2007;Maenosono et al 2007;Tsuang et al 2008;Reddy et al 2007;Heinlaan et al 2008;De Windt et al 2006;Lyon et al 2005). Besides, they exhibit biofilm inhibition.…”
Section: Msns Synthesis and Physico-chemical Characterizationmentioning
confidence: 44%
“…In addition, potential antibacterial effects of nanosized ZnO suspensions on bacteria were studied (Tayel et al, 2011Zhang et al, 2010Li et al, 2012;Reddy et al, 2007;Liu et al, 2009). Whilst chronic exposures up to 50 mg/L ZnONP did not affect the sigmoidal growth characteristics of E.coli OP50, strong antibacterial effects were observed at 100 mg/L ZnONP, a finding that was statistically significant (p≤0.05) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The harmful effects of ZnONPs are driven by their physicochemical properties (dissolution and formation rate, the morphology and chemical composition, surface reactivity, particle number) and the resulting physical damage caused by the aggregation and agglomeration of nanoparticles (Bai et al, 2010;Jiang et al, 2009;Zhang et al, 2010. The bio-kinetic behaviour and in vivo toxicity of ZnONP exposure has, to date, been investigated in several non-mammalian systems including in vitro cell-based assays (Sharma et al, 2012a,b;Ahamed et al, 2011;Wu et al, 2010), bacteria (Li et al, 2011;Reddy et al, 2007), algae (Franklin et al, 2007), plants (Lin and Xing, 2007), crustaceans (Poynton et al, 2011), fish (Bai et al, 2010), earthworms (Hooper et al, 2011) and nematodes (Khare et al, 2011;Ma et al, 2009;Ma et al, 2011;Roh et al, 2009;Wu et al, 2013). The nematode Caenorhabditis elegans, a powerful model organism due to the availability of a completely sequenced genome (Hillier et al, 2005) and many molecular genetics tools has been used in ecotoxicological research to study the molecular to organismal level responses to ROS and heavy metal challenges (Roh et al, 2006;Hughes and Sturzenbaum 2007;Swain et al, 2004Swain et al, , 2010Zeitoun-Ghandour et al, 2010; The roles of the metalloproteins metallothionein (MT) and phytochelatin (PC) are Furthermore, ZnONP mediated toxicity may result from the release of free ionic zinc (George et al 2010;Li et al, 2012;Poynton et al, 2011;Wang et al, 2009), which induces cellular damage via the generation of free reactive oxygen species (ROS), which in turn can promote pro-inflammatory effects Mocchegiani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on antibacterial activity among the various metal oxides nanoparticles, zinc oxide nanoparticles, have been found to be highly toxic. Many studies have shown that selective toxic nature of ZnONPs toward bacteria shows the minimal effect on human cells, which is suggested their potential uses in agricultural, food industries, diagnostics, surgical devices, and nanomedicine-based antimicrobial agents [21][22][23][24]. Among the several metal oxide nanoparticles, ZnONPs are emerged as booming nanoparticle due to their attractive characteristics and ideal properties in various biomedical applications.…”
Section: Introductionmentioning
confidence: 99%